Real‐World Clinical Outcomes in Patients with Locally Advanced or Metastatic Merkel Cell Carcinoma Treated in U.S. Oncology Clinical Practices: Results from SPEAR‐Merkel. (2nd July 2021) - Bhanegaonkar, Abhijeet; Liu, Frank X.; Boyd, Marley; Fulcher, Nicole; Kim, Ruth; Krulewicz, Stan; Smith, Jodi; Cowey, C. Lance
Abstract: Background: Immunotherapy (IO) has been associated with improved outcomes in patients with locally advanced Merkel cell carcinoma (laMCC) and metastatic Merkel cell carcinoma (mMCC). The primary objective of SPEAR‐Merkel was to explore treatment patterns, clinical outcomes, and health care resource utilization (HCRU) in patients with laMCC or mMCC initiating first‐line (1L) treatment with avelumab, non‐avelumab IO, or chemotherapy in a U.S. community oncology setting. Methods: Adult patients with laMCC or mMCC initiating 1L avelumab, non‐avelumab IO, or chemotherapy from January 1, 2015, to March 31, 2019, were identified from the U.S. Oncology Network electronic health care record database and followed up through September 30, 2019. Baseline characteristics and HCRU were analyzed descriptively, including physician‐stated overall response rate in the real‐world clinical setting. Kaplan‐Meier methods were used to measure duration of response, real‐world progression‐free survival (rwPFS), and overall survival (OS). Results: Among the overall population ( n  = 94), 28 received 1L avelumab (9 laMCC, 19 mMCC), 26 received 1L non‐avelumab IO (8 laMCC, 18 mMCC), and 40 received 1L chemotherapy (10 laMCC, 30 mMCC). The real‐world overall response rate was 64.3%, 61.5%, and 42.5%, respectively. From 1L treatment initiation, median rwPFS was 11.4, 8.1, and 6.1 months, and median OS was 20.2 months, not reached, and 14.7 months for the respective cohorts. Conclusion: SPEAR‐Merkel showed that patients with laMCC or mMCC treated with IO had improved outcomes compared with chemotherapy in clinical practice. The study provides insight on utilization and clinical outcomes associated with newer, more innovative therapies in clinical practice, which may help clinicians understand the variety of newer treatment options for both laMCC and mMCC. Implications for Practice: To the authors' knowledge, SPEAR‐Merkel is the first study to evaluate real‐world clinical outcomes in patients with locally advanced Merkel cell carcinoma (laMCC) and metastatic Merkel cell carcinoma (mMCC) receiving first‐line (1L) avelumab, non‐avelumab immuno‐oncology therapies, or chemotherapy in a real‐world setting. SPEAR‐Merkel showed clinical benefit for immuno‐oncology therapies compared with chemotherapy. The study provides insight on uses and clinical outcomes associated with innovative therapies in clinical practice, which may help clinicians understand the variety of newer treatment options for both laMCC and mMCC. The study is of particular importance as it shows that chemotherapy is still being used as 1L treatment despite its inferior clinical and safety profile. Abstract : The SPEAR‐Merkel study provides on current treatment patterns, real‐world clinical outcomes, and healthcare resource utilization in patients with locally advanced/metastatic Merkel cell carcinoma initiating first‐line treatment with avelumab, non‐avelumab immunotherapies, or chemotherapy within a large network of community‐based oncology practices in the U.S. Results are reported here.